Loss of interactions between p53 and survivin gene in mesenchymal stem cells after spontaneous transformation in vitro. (June 2016) - He, Liu; Zhao, Fangyu; Zheng, Yong; Wan, Yu; Song, Jian
Abstract: Mesenchymal stem cells (MSC) from various animals undergo a spontaneous transformation in long-term culture. The transformed MSCs are highly tumorigenic and are likely to be the tumor-initiating cells of sarcoma. To explain why the transformed MSCs become tumorigenic, the present study investigated the characteristics of rat MSCs before and after spontaneous transformation. It was shown that although the transformed MSCs maintained typical surface markers of MSC, they exhibited some cancer stem cell-like characteristics such as loss of contact inhibition and multi-potency to mesenchymal lineages, and acquirement of ability of anchorage-independent growth. The expression of a key senescence regulator p16 almost disappeared, but the other one, p53 abnormally increased in the transformed MSCs. ChIP assay demonstrated that a normal negative regulation of p53 on survivin gene disappeared in the transformed cells due to a lack of p53 binding to the promoter of survivin gene. DNA sequencing revealed that the p53 gene in transformed MSCs was not a wild-type, but a 942C > T mutant with the mutation located in the sequence coding p53 protein's DNA-binding domain. These findings indicate that the transformed MSCs express high levels of a p53 mutant that loses the ability to bind survivin gene, leading to an abnormally upregulated expression of survivin, which is a key reason for the cell's unlimited proliferation.